PRINSIP-PRINSIP MANAJEMEN TENAGA PENDIDIK DAN KEPENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIKAN: PRINCIPLES OF EDUCATOR MANAGEMENT AND EDUCATION TO IMPROVE THE QUALITY OF EDUCATION - Syukri, Makmur; Delastri, Yefrineng; Anggraini, Desi; Putri, Desi Sandra; Marzelni, Marzelni (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Abstract: Management of educational personnel, which includes teachers and educational personnel, is a necessity that must be carried out by school administrators in order to utilize educational personnel effectively and efficiently in order to achieve the best results. The ability to search, place, evaluate, direct, motivate and develop the abilities of each teacher and employee, as well as the ability to align individual and organizational goals, are aspects that a school manager is expected to have according to needs. this understanding. The quality of the education and learning process can be studied from two different points of view, namely the quality of the components and the quality of the administration of school institutions. If these components are not managed "well" and "appropriately" in accordance with the educational and teaching program (school program) that has been determined, then it is certain that the educational and teaching objectives will not be achieved. This occurs even though the components are supportive, such as the availability of adequate facilities and infrastructure, as well as sufficient funds. will be achieved successfully. Therefore, management principles are an important instrument that can show the extent of teacher success or failure in achieving learning goals and school programs. This is intended to enable school principals to carry out their role as leaders, which enables them to carry out school-based management to improve the quality of education provided in schools throughout the country. Keywords : Principles of management of teaching and educational staff, quality of education